Truck Routing for Waste Collection: A Case Study of Tha Ruea District, Phra Nakhon Si Ayutthaya Province - Kanogkan Leerojanaprapa; Jinnapat Thongmak; Thanaporn Disada; Kittiwat Sirikasemsuk (Warasan Witthayasat Latkrabang (Online), 2024)
At present, waste collection is a routine and one of the major municipal functions that needs to improve efficiency. Tha Ruea Subdistrict of Phra Nakhon Si Ayutthaya Province aims to improve efficiency of the vehicle routing of garbage trucks. Therefore, the objective of this research is to suggest the optimal route by dividing this study into two scenarios: Scenario 1: re-route based on four original route zones (A - D zone) and Scenario 2: combining into 2 route zones (E and F zone) before re-routing. This research compared the original transport routes with the Nearest neighbor algorithm, Saving algorithm, Evolutionary algorithm, and Linear programming method. The results concluded that in the first scenario, the Linear programming approach provides the shortest routes in all zones and shows the same route based on Evolutionary algorithm for C zone by reducing the total distance by 0.25, 1.67, 0.72, and 0.7 kilometers, respectively. For Scenario 2, use routing zone integration by merging zones A and B into route E zone and combining zones C and D into route F zone. The study found that the Linear programming approach results in the shortest route in both zones, which can be reduced from the original route by 16.51 kilometers and 15.39 kilometers, or by 43.54% and 38.15% respectively. The total distance was reduced from 78.27 kilometers to 46.37 kilometers per day or decreased by 40.76%.
Keywords: Municipal Solid Waste Management; Recycling and Waste Management Techniques; Belt and Road Initiative